Prevalence of Nocturia and Its Association with Sleep Quality Among Medical Students During the Covid-19 Pandemic: A Cross-Sectional Study - Daryanto, Besut; Lasdianto, Triana Amelia; Rakhmani, Alidha Nur (Department of Urology, Faculty of Medicine, Universitas Brawijaya, 2026)
Introduction. Nocturia is the most common lower urinary tract disease that is characterized by waking up to urinate more than once during the main sleep period and its prevalence increases with age. This study aimed to investigate frequency, bothersome and relation of nocturia with sleep quality during COVID-19 pandemic in medical students. Methods. This study used a cross-sectional approach and an analytical observation method by distributing questionnaires. Questions include demographic characteristics, frequencies of nocturia, and bother scores related to nocturia. Results. Data on 90 individuals eligible for statistical analysis. The average age was 19.24 ± 1.08 years. Overall nocturia prevalence was 38.8% medical students had nocturia. The nocturia rate was 42.2% and 35.56% in men and women, respectively (p = 0.642). The frequency of nocturia per night was 24.4%, 13.3% and 0.01% (1, 2, and 4 times, respectively). Conclusion. Nocturia is common among medical students, especially men and it is not related with sleep quality.